Ontogeny of the Alligator Cartilago Transiliens and Its Significance for Sauropsid Jaw Muscle Evolution - Tsai, Henry P.; Holliday, Casey M. (PLOS ONE, 2011)
The cartilago transiliens is a fibrocartilaginous structure within the jaw muscles of crocodylians. The cartilago transiliens slides between the pterygoid buttress and coronoid region of the lower jaw and connects two muscles historically identified as m. pseudotemporalis superficialis and m. intramandibularis. However, the position of cartilago transiliens, and its anatomical similarities to tendon organs suggest the structure may be a sesamoid linking a single muscle. Incompressible sesamoids often form inside tendons that wrap around bone. However, such structures rarely ossify in reptiles and have thus far received scant attention. We tested the hypothesis that the cartilago transiliens is a sesamoid developed within in one muscle by investigating its structure in an ontogenetic series of Alligator mississippiensis using dissection, 3D imaging, and polarizing and standard light microscopy. In all animals studied, the cartilago transiliens receives collagen fibers and tendon insertions from its two main muscular attachments. However, whereas collagen fibers were continuous within the cartilaginous nodule of younger animals, such continuity decreased in older animals, where the fibrocartilaginous core grew to displace the fibrous region. Whereas several neighboring muscles attached to the fibrous capsule in older individuals, only two muscles had significant contributions to the structure in young animals. Our results indicate that the cartilago transiliens is likely a sesamoid formed within a single muscle (i.e., m. pseudotemporalis superficialis) as it wraps around the pterygoid buttress. This tendon organ is ubiquitous among fossil crocodyliforms indicating it is a relatively ancient, conserved structure associated with the development of the large pterygoid flanges in this clade. Finally, these findings indicate that similar tendon organs exist among potentially homologous muscle groups in birds and turtles, thus impacting inferences of jaw muscle homology and evolution in sauropsids in general.